ANALISIS KEBERLANJUTAN SOSIAL UMKM KOPI BUBUK PEREMPUAN WIRAUSAHA DI SUMATERA BARAT - Ninda Novita; Burhanuddin; Rachmat Pambudy (Jurnal Agribisnis Indonesia, 2025)
Agroindustry-based MSMEs are a "leading sector" in agricultural development. MSMEs play a role in enhancing human resource competitiveness, creating new business opportunities, and absorbing the workforce. The increasing coffee consumption currently drives competition in both local and international coffee industries to better understand consumer preferences. Although the majority of micro-scale black coffee agroindustries in West Sumatra are managed by women, they have sustained operations since 1958 while facing competitors. This study aims to analyze the effect of social capital on social sustainability and the effect of social capital on social sustainability through entrepreneurial orientation. Data collection was conducted using a census method involving 160 respondents from black coffee MSMEs. Data were analyzed using SmartPLS 4.0. The study found that most female entrepreneurs (90.7 percent or 145 individuals) are aged 25–64, with 57.5 percent having completed senior or vocational high school. Most have less than 10 years of work experience. Social capital positively impacts social sustainability (0.773, T-Statistic 17.438), indicating a significant relationship. Entrepreneurial orientation shows a weak, insignificant effect (0.063, T-Statistic 0.111). Social capital has a direct influences on social sustainability, while entrepreneurial orientation does not significantly mediate this relationship. Enhancing social sustainability in women-led MSMEs requires fostering social relationships and empowering women for sustainable development.